Physical determinants of cell organization in soft media - Schwarz, Ulrich S.; Bischofs-Pfeifer, Ilka (Medical engineering & physics, 2005)
Cell adhesion is an integral part of many physiological processes in tissues, including development, tissue maintenance, angiogenesis, and wound healing. Recent advances in materials science (including microcontact printing, soft lithography, microfluidics, and nanotechnology) have led to strongly improved control of extracellular ligand distribution and of the properties of the micromechanical environment. As a result, the investigation of cellular response to the physical properties of adhesive surfaces has become a very active area of research. Sophisticated use of elastic substrates has revealed that cell organization in soft media is determined by active mechanosensing at cell-matrix adhesions. In order to determine the underlying mechanisms, quantification and biophysical modelling are essential. In tissue engineering, theory might help to design new environments for cells.
Gesehen am 15.12.2017